THE INFLUENCE OF VOCABULARY MASTERY AND READING STRATEGY ON STUDENTS’ READING ABILITY: An Ex Post Facto Study at the 4th semester students of department of English Literature, STBA JIA Bekasi. - Esterria Romauli Panjaitan; Winda Lutfiyanti; Inta Masni Sinaga (Wiralodra English Journal, 2024)
The research conducted at 4th semester aimed to investigate the influence of vocabulary mastery and reading strategy on students’ reading ability. Ex Post Facto study was implemented, and a simple random sampling technique was used which sample consisted of 3 classes. Data collection was achieved through questionnaires and tests, ensuring instrument validity and reliability. Product Moment Correlation and Multiple Regression were used in data analysis. The results showed that there is significant influence of vocabulary mastery on reading ability with 34,26% of the effective contribution, a significant influence of reading strategy on reading ability with 7,96 of the effective contribution, and a substantial influence on vocabulary mastery and reading strategy combined on the reading ability with 42.3% of the total effective contribution. These findings highlight the importance of vocabulary mastery and reading strategy in improving students' reading ability. When constructing teaching materials and ways to improve students' reading ability, lecturers and curriculum designers should keep these variables in mind. It is suggested for future researchers to explore more advanced methodologies and treatments to improve vocabulary and reading knowledge, perhaps leading to even greater improvements in students' reading ability. Additionally, further research can still provide insights for educators and students.